Method And Results For Developing A Device For Electro technological Treatment Of Apple Trees In Intensive Orchards (Texas Journal of Engineering and Technology, 2026)
This study presents the development and evaluation of an electrotechnological device for controlling aphids on apple trees in intensive orchards using UV-C radiation (253.7 nm). The research is based on an analysis of plant diseases, pest control methods, and electrophysical approaches. Field experiments showed that treatment efficiency depends on distance and exposure time. The highest efficacy (98.1%) was achieved at a 0.3 m distance with a double 20-minute treatment, while increasing the distance reduced effectiveness. Economic analysis demonstrated significant cost savings, with the UV-C method reducing expenses by 40,734,000 UZS over three years compared to chemical treatment. The device is simple, portable, energy-efficient, and environmentally safe, making it an effective alternative to chemical pest control.